Palliative needs for heart failure or chronic obstructive pulmonary disease: Results of a multicenter observational registry. (1st April 2015) - Gavazzi, Antonello; De Maria, Renata; Manzoli, Lamberto; Bocconcelli, Paolo; Di Leonardo, Antonio; Frigerio, Maria; Gasparini, Stefano; Humar, Franco; Perna, Gianpiero; Pozzi, Roberto; Svanoni, Fausto; Ugolini, Marcello; et al.
Abstract: Background: Heart failure (HF) and chronic obstructive pulmonary disease (COPD) share a common organ failure trajectory marked by prognostic uncertainty, which is a barrier to appropriate provision of palliative care. We describe in a prospective cohort from specialist hospital services the epidemiology and late clinical course of these chronic diseases to trace criteria for transition to palliative care in the community. Methods and results: Seven centers enrolled 267 patients with advanced HF (n = 174) or COPD (n = 93) using common (multiple hospitalizations or severely impaired functional status or cachexia) and disease-specific (HF: systolic dysfunction, NYHA classes III–IV, end-organ hypoperfusion; COPD: very severe airflow obstruction, hypoxemia, hypercapnia, or long-term oxygen therapy) entry criteria. These patients represented 7.2% and 13% respectively of the overall HF and COPD population hospitalized during one year. They showed similar symptom burden, functional and quality of life impairment, recurrent hospitalizations, and 6-month mortality (39% and 37%, respectively). Organ failure progression was the cause of death in > 75%. In-hospital overall stay during the previous year was the main mortality predictor in both. Disease-specific predictors included anemia, hyponatremia, no beta-blockers in HF; older age, hypercapnia in COPD. Conclusions: Patients with advanced HF/COPD represent almost 10% of subjects hospitalized yearly with a primary diagnosis of HF or COPD, have similarly impaired functional status, disabling symptoms and reduced survival. Overall days spent in-hospital during the previous year, a "red flag" in the late clinical course of both diseases, might be used as a simple, reliable screening tool for appropriate transition to palliative care in the community. Highlights: Advanced HF or COPD shows overlapping disabling symptoms and functional impairment. Reduced survival and prolonged readmissions are similarly frequent. Time spent in-hospital in the previous year is the main predictor of mortality in both. Prolonged/repeated admissions may serve as screening tool for palliative referral.